Cooperation model in the electricity energy market using bi-level optimization and Shapley value - Luceny Guzmán Acu\~na; Diana Ramírez Ríos; Carlos D. Paternina-Arboleda; Esneyder González Ponzón (Operations Research Perspectives, 2018)
In this paper, a cooperation model between a generating company and several marketers is presented. The model considers two cooperation schemes. The first finds the optimal decision for the generating company and the group of marketers in terms of maximization of their profits, based on bi-level optimization. Second scheme proposes the cooperation among the marketers, whose objective is to serve a common set of consumers and to increase their profits through cooperation, with respect to the profit gained individually. Profit of the marketers group are divided among them, based on the Shapley value. The model was solved using GAMS and Visual Studio Tools for Office and was validated through a case study in a region in Colombia. The results of the study showed that implementing these cooperation structures brings additional economic benefits to the cooperating agents.
Keywords: 330; Cooperation models; Energy market; Bi-level optimization; Shapley value